1969
DOI: 10.1037/h0028143
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of memory.

Abstract: This upper-level text presents a classical view of verbal learning and memory. Organized around the theme of memory as comprised of various attributes, or types of information, it thoroughly covers all major phenomena in memory research. Original research is used extensively, much of it derived from Dr. Underwood's own laboratory and classroom studies.• Outstanding authorship by a leader in the field of memory research • Emphasis on factors that influence both short-and long-term forgetting « Research methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
367
3
4

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 569 publications
(387 citation statements)
references
References 38 publications
13
367
3
4
Order By: Relevance
“…Within this "modal model" of information processing, information that receives attention and elaboration is more likely to be subsequently available for retrieval (Brown & Craik, 2000). More important, memories are not believed to be stored in an all-or-none form, ala a storehouse model, but as a collection of attributes, which may include factors such as the time and place of the experience, the initial phoneme of a word, or the affective valence that a word carries (Underwood, 1969). Access to these attributes may determine whether a memory is retrieved, and research on phenomena such as tip-of-the-tongue has suggested that individual attributes may be sufficient to support successful memory retrieval (Koriat, Levy-Sadot, Edry, & de Marcas, 2003).…”
Section: Background From Cognitive Psychologymentioning
confidence: 99%
“…Within this "modal model" of information processing, information that receives attention and elaboration is more likely to be subsequently available for retrieval (Brown & Craik, 2000). More important, memories are not believed to be stored in an all-or-none form, ala a storehouse model, but as a collection of attributes, which may include factors such as the time and place of the experience, the initial phoneme of a word, or the affective valence that a word carries (Underwood, 1969). Access to these attributes may determine whether a memory is retrieved, and research on phenomena such as tip-of-the-tongue has suggested that individual attributes may be sufficient to support successful memory retrieval (Koriat, Levy-Sadot, Edry, & de Marcas, 2003).…”
Section: Background From Cognitive Psychologymentioning
confidence: 99%
“…By this view, speaker normalization becomes a testable hypothesis, rather than an assumed process, equally evidenced by positive or null effects. As it happens, many contemporary models resemble Semon's (1909Semon's ( /1923 theory, positing parallel access to stored traces (Eich, 1982;Gillund & Shiffrin, 1984;Hintzman, 1986Hintzman, , 1988Medin & Schaffer, 1978;Nosofsky, 1984Nosofsky, , 1986Underwood, 1969). Such theories are partly motivated by common findings of memory for "surface" details of experience.…”
Section: Speaker Normalizationmentioning
confidence: 99%
“…This model takes episodic storage to a logical extreme, assuming that all experiences create independent memory traces that store all perceptual and contextual details (cf. Underwood, 1969). Despite their separate storage and idiosyncratic attributes, aggregates of traces activated at retrieval create behavior.…”
Section: The Episodic Lexicon?mentioning
confidence: 99%
“…Attributes have been divided into two general classes (Underwood , 1969), those which are involved in the retrieval of memories (the associative or retrieva l attributes) and those involved in discriminating among memories . This distinction refers to recall versus recognition .…”
Section: Individual Differences and Attributes Of Memorymentioning
confidence: 99%